2007
DOI: 10.1016/j.ypmed.2007.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative risk factors for adolescent alcohol misuse and its perceived consequences among 16 to 20 year old adolescents in Switzerland

Abstract: Risk factors for adolescent alcohol misuse are cumulative and can be synthesized into an individual score correlated with the likeliness of misuse. A further indication of the validity of this score is its linear relationship with self-reported problems related to drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
4
26
2
3
Order By: Relevance
“…The prevalence of alcohol consumption among Thai adolescents (past-year drinking = 25.5% in boys and 14.5% in girls) was lower than was reported in other countries, e.g., 48.1% for moderate drinking in the past 12 months among Swiss students (Zufferey et al, 2007), 26% for any alcohol intake in the last 30 days for Asian and Pacific Islander adolescents in California (Kim and McCarthy, 2006), 44.9% for drinking in the past 30 days among high school students in U.S.A. (Miller et al, 2007), and 81% for drinking in the past 4 weeks among New Zealand university students (Kypri et al, 2008). The prevalences of current drinking across school years in our study were substantially lower than those reported in the U.S.…”
Section: Discussioncontrasting
confidence: 56%
“…The prevalence of alcohol consumption among Thai adolescents (past-year drinking = 25.5% in boys and 14.5% in girls) was lower than was reported in other countries, e.g., 48.1% for moderate drinking in the past 12 months among Swiss students (Zufferey et al, 2007), 26% for any alcohol intake in the last 30 days for Asian and Pacific Islander adolescents in California (Kim and McCarthy, 2006), 44.9% for drinking in the past 30 days among high school students in U.S.A. (Miller et al, 2007), and 81% for drinking in the past 4 weeks among New Zealand university students (Kypri et al, 2008). The prevalences of current drinking across school years in our study were substantially lower than those reported in the U.S.…”
Section: Discussioncontrasting
confidence: 56%
“…This study adds to the growing body of literature on negative adult social and behavioral consequences of adolescent drinking (Oesterle et al, 2004;Staff et al, 2008, Zufferey et al, 2007. In addition to reinforcing the importance of preventing frequent drinking among youth, fi ndings suggest that violence prevention efforts should focus on the role of early frequent drinking and later problematic drinking.…”
Section: Discussionmentioning
confidence: 66%
“…Underage alcohol consumption also can be quite dangerous. Underage drinkers are at heightened risk for injuries and emergency room visits, suicidality, interpersonal problems with family and friends, school problems, risky sex, and risky driving (Jacobus, Bava, Cohen-Zion, Mahmood, & Tapert, 2009;Teplin et al, 2005;Windle & Windle, 2005;Zufferey et al, 2007). Moreover, the more an adolescent drinks, the more likely that adolescent as an adult will experience alcohol dependence and other substance abuse, antisocial behavior, legal problems, vocational problems and unemployment, comorbid disorders, and interpersonal problems with family and friends (Danielsson, Wennberg, Tengström, & Romelsjö, 2010;Hicks, Iacono, & McGue, 2010).…”
Section: Alcohol Use Among Hispanic=latino Youthmentioning
confidence: 99%